Local Public Good Provision, Municipal Consolidation, and National Transfers - Robert Dur; Klaas Staal (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2006)
We analyze a simple model of local public good provision in a country consisting of a large number of heterogeneous regions, each comprising two districts, a city and a village. When districts remain autonomous and local public goods have positive spillover effects on the neighboring district, there is underprovision of public goods in both the city and the village. When districts consolidate, underprovision persists in the village (and may even become more severe), whereas overprovision of public goods arises in the city as urbanites use their political power to exploit the villagers. From a social welfare point of view, inhabitants of the village have insufficient incentives to vote for consolidation. We examine how national transfers to local governments can resolve these problems.
urn:nbn:de:bvb:19-epub-13465-2
Keywords: D7; H2; H7; R5; 330; local public goods; municipal consolidation; voting; intergovernmental transfers